Arabic Learning Outcomes among Boarding and Non-Boarding Students at MAS DDI Pattojo: A Comparative Study - Andi Nurul Hidayatullah; Munawarah Munawarah; Nurwan Nurwan; Hikmatul Azizah (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
This study aims to: (1) describe the Arabic learning outcomes of boarding students at MAS DDI Pattojo; (2) describe the Arabic learning outcomes of non-boarding students; and (3) compare the learning outcomes of both groups. The research used a quantitative method with sociological and pedagogical approaches. The population consisted of 77 students from grades X and XI, with a saturated sampling technique involving 45 boarding students and 32 non-boarding students. Data were collected through observation, tests, and documentation, while data analysis applied descriptive and inferential statistical techniques. The findings show that both groups demonstrated relatively low performance in Arabic reading skills (mahārah qirā’ah). Boarding students achieved an average score of 30.89, while non-boarding students obtained an average score of 29.69. Furthermore, the Mann-Whitney U test revealed no significant difference between the two groups, as indicated by an Asymp. Sig. value of 0.615, which is greater than 0.05. These results indicate that the place of residence, whether boarding or non-boarding, is not a major factor influencing Arabic learning outcomes at MAS DDI Pattojo, suggesting that other educational or instructional factors may play a more significant role.